UJI ORGANOLEPTIK TEPUNG JANENG (Dioscorea hispida Dennst) SEBAGAI SUBSTITUSI PADA KUE SEUPET - Evinopita Taib; Eva Nauli Taib; Yuyun Eva Sartika (Prosiding Seminar Nasional Biotik, 2022)
In the context of developing food security, the government must be able to provide sufficient food for the entire population, especially from domestic products in sufficient quantity and variety. Gadung (Dioscorea hispida Dennst) from the family Dioscoreaceae in the Acehnese language is known as janeng. The purpose of this study was to describe the organoleptic assessment of janeng flour. This research method is organoleptic test analysis of janeng flour and seupet janeng. The organoleptic assessment involved 30 teachers of SMK Negeri 4 Aceh Barat Daya as panelists. The results of the study were the use of janeng flour in the manufacture of seupet janeng to be one way of utilizing agricultural commodities and increasing the selling value of janeng flour. All panelists really liked the taste, color and aroma of janeng flour. Likewise for the preparations, namely seupet janeng as well as the hedonic number 34% really like it and 60% like it.